EFL Learners’ Difficulties in Speaking English - Afi Normawati; Dwitiya Ari Nugrahaeni; Noor Sahid Kusuma Hadi Manggolo; Allvian Ika Fiki Susanto (English Language and Education Spectrum, 2023)
This study aims to investigate the difficulties faced by EFL leaners’ in speaking English. The identification of the difficulties covers the six aspects of speaking skill, namely, pronunciation, grammar, vocabulary, fluency, comprehension, and task. The The participants of the study were the first semester non-English Department students of Universitas Tidar who took English as General Course Class. The research data were collected from the students’ spoken production and responses to the questionnaire. The results of the study show that there are three major difficulties identified from the students’ responses. They are grammar (48%), pronunciation (27%), vocabulary (12%), and the other aspects less than 10%.